Artifact. Art-Object. Argument. An Object in Fine Arts: Acquisition of New Meanings in Modern and Contemporary Eras - Klyushina, Elena V.; Mal’tseva, Svetlana V.; Staniukovich-Denisova, Ekaterina Iu. (Actual Problems of Theory and History of Art, 2018)
Summing up the results of the conference “Actual Problems of Theory and History of Art VII”, held in autumn 2016 in the State Hermitage and Saint Petersburg State University, the authors of this article note a significant extension of the definitional possibilities of the terms “artifact” and “art object” in Modern and Contemporary eras. The main theoretical conclusions are made with an eye for the works of T. de Duve, J. Baudrillard, T. Adorno, G. Dickie and other authors. Turning to a direct analysis of the texts included in the collection of articles, the authors point to a variety of analytical approaches chosen by the participants in the conference to define the terms “artifact” and “art object” in the fine arts of the 17th-21st centuries.